Greenhouse gases in urban areas - (:unkn) unknown (BULGARIAN ACAD SCIENCE, 2016)
The majority of citizens live in urban areas that dominate the economy and energy use. People living in these areas can affect the balance of nature since the gradual increase in the earth's surface temperature is caused predominantly by human activity. Humans cause the emission of gases such as carbon dioxide through exhaust from cars and power plants. If this negative effect continues, climate change due to global warming is inevitable. While CO2 concentration was around 250-280 parts per million (ppm) in the late 1800s, according to the National Oceanic Atmospheric Administration, it reached 380 ppm in the 2000s and 400 ppm in 2015. If we do not act and if emissions continue to increase, the global mean temperature may increase by over 30C by 2030. In this study, GHG emissions for 2020 are predicted for some countries then arithmetic means and standard deviations for GHG emissions are calculated by Excel. Data on GHG emissions for Europe, Turkey and the U.S. are used for the periods 2004-2013, 1990-2010 and 2000-2011, respectively. Chemical processes to mitigate GHG in the atmosphere are explained. Oxidation and methanol synthesis are useful processes to decrease the amount of GHG. Therefore, energy consumption in urban areas is very important. Reducing energy consumption in cities is possible by increasing the density (increasing the number of people per square meter in the city), the use of public transport such as subways, buses, trams, and light rail, and the use of energy derived from waste.
Keywords: Urban; Global warming; Energy consumption; Air quality